Investigating Teacher Perceptions Regarding Their Competencies in the 5.0 Era - Tsabitah, Noviana Aribah; Sudarsi, Sri; Affanda, Elma Firza; Al-Fatih, Muhammad Hasan (Universitas Muhammadiyah Yogyakarta, 2024)
Teachers play a crucial role in education by imparting knowledge, fostering critical thinking, and creating positive learning Education has experienced a significant transformation along with changing times, especially in the current 5.0 era. To prepare for this, teachers are expected to have competency 5.0. However, not many teachers are ready to face the challenges that will be faced in the 5.0 era. Therefore, this research aims to investigates teachers' perceptions regarding their competencies, challenges and ways to overcome the challenges faced by teachers in facing the 5.0 era. This research used a qualitative descriptive research design. Data was collected through in-depth interviews with three EFL teachers in the English Language Education Department. The tentative findings of this research are 1. Communication Competencies, 2. Leadership and Resilience Competencies, 3. Curiosity Competencies, and 4. Reading Comprehension Skills. These findings are useful for improving the quality of teachers so they can provide effective learning strategies to students.